2007
DOI: 10.1021/ja077233b
|View full text |Cite
|
Sign up to set email alerts
|

High Gas Storage Capacities for Ionic Liquids through Chemical Complexation

Abstract: Gases with sufficient Lewis acidity or basicity form weak and reversible complexes with carefully selected ionic liquids. We have prepared ionic liquid complexes with PH3 and BF3 that provide large gas capacities in the liquid phase at low pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 16 publications
2
74
0
2
Order By: Relevance
“…Tempel et al [178] demonstrated that a reversible complexation of Lewis basic gases like BF 3 with ionic liquids is possible, permitting the use of ionic liquids as a transport media that allows the reversible absorption and desorption of this dangerous compound. They investigated the absorption of PH 3 and BF 3 in two different ionic liquids, the 1-butyl-3-methylimidazolium trichlorodicuprate [C 4 mim][Cu 2 Cl 3 ] and the 1-butyl-3-methylimidazolium tetrafluoroborate [C 4 mim][BF 4 ], respectively.…”
Section: The Soft-saft Equation Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…Tempel et al [178] demonstrated that a reversible complexation of Lewis basic gases like BF 3 with ionic liquids is possible, permitting the use of ionic liquids as a transport media that allows the reversible absorption and desorption of this dangerous compound. They investigated the absorption of PH 3 and BF 3 in two different ionic liquids, the 1-butyl-3-methylimidazolium trichlorodicuprate [C 4 mim][Cu 2 Cl 3 ] and the 1-butyl-3-methylimidazolium tetrafluoroborate [C 4 mim][BF 4 ], respectively.…”
Section: The Soft-saft Equation Of Statementioning
confidence: 99%
“…Symbols represent the experimental data from Ref. [178]. Comparison between original calculations with no association (dashed lines) and association (solid lines).…”
Section: The Soft-saft Equation Of Statementioning
confidence: 99%
“…Furthermore, the possibility of tuning their properties, through the simple combination of different ions, allows the design of specific ILs for target applications. As a result of their tailoring ability and unique properties, ILs have been studied for various application, such as lubricants [7], gas storage media [8,9], solvents in multiphasic homogeneous catalytic reactions [5,10], solvent media and catalysts in heterogeneous reactions [11], extraction solvents of compounds of biotechnological and analytical interest [12,13], potential solvents in extractive distillation processes to separate water-ethanol mixtures [14], enhanced candidates to dissolve and process biomass [15], among many other exploratory purposes. Notwithstanding their academic interest, ILs have caught the industry interest and are currently being used in some industrial processes and products [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ionic liquids (ILs) have attracted considerable attention as solvents, [1][2][3] catalysts, [4][5][6][7] sorbents, [8][9][10] materials, [11][12][13] etc., owing to their remarkable properties, including extremely low vapor pressure, high thermal stability, wide temperature range as liquids, and high ionic conductivity. [14][15][16][17] ILs are also recognized as designable liquids, because their physical and chemical properties are facilely tuned by different combinations of the cation and the anion.…”
Section: Introductionmentioning
confidence: 99%